The long-term effects of voting for autocracy: evidence from Russia - Northmore-Ball, K; Tertytchnaya, K (Elsevier, 2023)
Do different Russian generations differ in their propensity to vote? Drawing on evidence from Soviet and post-Soviet elections, we consider how early-life electoral experiences influence voters’ life-long voting propensity. The empirical analysis relies on a harmonized dataset of survey data covering all national elections between 1991 and 2018. We estimate differences in turnout propensity across generations using several forms of age–period–cohort analysis including hierarchical age-period-cohort analysis and semi-parametric generalized additive models. Findings suggest that generations voting for the first time in elections taking place between 1946–1966 have a higher propensity to vote than others. Complementing quantitative evidence with extensive description, we propose that state-led mobilization efforts under Communism and the opportunity to vote in regularly held elections may account for these effects. Our research has implications for research on the consequences of authoritarian elections and their impact on long-term voter behaviour.